A comparative study of visual schemas of Persian and Kurdish children's poems - Forozan bhramzadeh (پژوهشنامه ادبیات کردی)
One of the semantic approaches is pictorial design. In this way, human experiences from the surrounding world create conceptual constructions in his mind that can be transferred to the level of language, hence, tangible and embodied experiences within the conceptual system lead to the production of image schemas. The present article aims to examine some processes and conceptual constructions in cognitive semantics in the form of visual schemas with a comparative approach, and for this purpose, it has selected Persian and Kurdish children's poems to show that in Persian and Kurdish children's literature, conceptual constructions How they help to understand abstract areas in children's poetry. The findings of the research show that most of the image schemas in Persian and Kurdish children's poems are of movement type and the reason can be found in the theme of the poems. Because concepts such as play, learning, and work require movement, movement, and activity. In addition to this, the visual design of power has taken the second place in children's poems after the movement design. This is also due to the educational and educational approach that is taught to children in order to achieve a desirable and ideal world. Volumetric design also has a significant presence in Persian and Kurdish children's poems. The presence of this scheme is in line with the expression of achieving abstract concepts such as sadness, peace, happiness and so on. . . It is in a tangible and tangible place